Combined Transcriptome and Metabolome Analysis of Musa nana Laur. Peel Treated With UV-C Reveals the Involvement of Key Metabolic Pathways - Chen, Ming-zhong; Zhong, Xu-Mei; Lin, Hai-Sheng; Qin, Xiao-Ming (Frontiers in Genetics, 2022)
An increasing attention is being given to treat fruits with ultraviolet C (UV-C) irradiation to extend shelf-life, senescence, and protection from different diseases during storage. However, the detailed understanding of the pathways and key changes in gene expression and metabolite accumulation related to UV-C treatments are yet to be explored. This study is a first attempt to understand such changes in banana peel irradiated with UV-C. We treated Musa nana Laur. with 0.02 KJ/m2 UV-C irradiation for 0, 4, 8, 12, 15, and 18 days and studied the physiological and quality indicators. We found that UV-C treatment reduces weight loss and decay rate, while increased the accumulation of total phenols and flavonoids. Similarly, our results demonstrated that UV-C treatment increases the activity of defense and antioxidant system related enzymes. We observed that UV-C treatment for 8 days is beneficial for M. nana peels. The peels of M. nana treated with UV-C for 8 days were then subjected to combined transcriptome and metabolome analysis. In total, there were 425 and 38 differentially expressed genes and accumulated metabolites, respectively. We found that UV-C treatment increased the expression of genes in secondary metabolite biosynthesis related pathways. Concomitant changes in the metabolite accumulation were observed. Key pathways that were responsive to UV-C irradiation include flavonoid biosynthesis, phenylpropanoid bios6ynthesis, plant-pathogen interaction, MAPK signaling (plant), and plant hormone signal transduction pathway. We concluded that UV-C treatment imparts beneficial effects on banana peels by triggering defense responses against disease, inducing expression of flavonoid and alkaloid biosynthesis genes, and activating phytohormone and MAPK signaling pathways.